Fabrication and characterization of micro fluidic based fiber optic refractive index sensor - Hamid, I.S.L. Abdul; Kamil, Y. Mustapha; Manaf, A. Abd; Mahdi, M.A. (Elsevier, 2017)
A refractive index sensorwas proposed by using 3 dimension (3D) grayscale lithography technique. Optical fiber with taper diameter of 12 μm was embedded in a closed microfluidic channel. Taper area of optical fiber is in floating condition at the center of micro channel. Grayscale variation range used for this sensor was 70%–74% and thickness variation 430 μm–694 μm was achieved. The dimension of the sensor was 7.5 cm in length and 2 cm in width. Fabricated sensor was characterized with air condition and solution concentration from 0.1 M to 1 M. A sensitivity of 1457 nm/RIU is achieved. The measured results show a good repeatability and low temperature cross-sensitivity.